The Effect of Warm Compress on Low Back Pain during Pregnancy - Shinta Novelia; Rukmaini; Siti Anisah (Nursing and Health Sciences Journal (NHSJ), 2021)
Back pain is one of the discomforts experienced by pregnant women in the third trimester. From some of the discomforts of pregnant women in Kilasah Village, 32 samples of TM III pregnant women who experienced back pain were taken. This study aims to observe the intensity of back pain before and after being given warm compresses. This study aimed to determine the effect of warm compresses on lower back pain among third trimester pregnant women who do pregnant exercise in Kilasah Village, Kilasah Health Center Work Area, Kasemen District, Serang City. This study used a quasi-experimental research design with a control group design. The sample in this study was pregnant women of third trimester in the village of Kilasah. The samples was 32 respondents who were divided into two groups; 16 intervention groups and 16 control groups. The results of this study indicate that there was a difference in the level of low back between the intervention group and the control group (p value = 0.000). It is hoped that the results of this study can become the basis for developing methods to reduce low back pain in third trimester pregnant women.